An Efficiency Comparison of Regional Employment Offices Operating under Different Exogenous Conditions - José V. Ramirez; Anatoli Vassiliev (Swiss Journal of Economics and Statistics, 2007)
This paper investigates the technical efficiency differences of a sample of regional employment offices (REOs) across Swiss cantons. Regular job-search assistance, registration and matching of unemployed workers with job vacancies performed by employment offices are all important active labour market policies (ALMPs) which are often ignored in the literature evaluating the impact of active measures. The analysis is carried out by means of a stochastic production frontier model estimated on a panel of employment offices observed over the period between November 2000 and December 2001. The results show that the specific exogenous conditions exercise a strong influence over the technical efficiency of each employment office. Even though these conditions affect significantly the relative performance of regional employment offices, the managerial efficiency component does remain important. Hence, employment offices may improve their efficiency by adopting better managerial practices. Finally, the job placement process is characterised by decreasing returns to scale.
Keywords: C23; D24; J68; 330; Regional employment offices; technical efficiency; exogenous conditions; stochastic frontier production function